Synthesis and characterization of PVDF‐coated cotton‐derived hard carbon for anode of Li‐ion batteries. (10th May 2019) - Li, Lingfang; Fan, Changling; Tang, Yucai; Zeng, Bin
Summary: A carbonized cotton that is coated by pyrocarbon of Polyvinylidene Fluoride (PVDF) (HC/P) was synthesized by a facile method. Its microstructure and electrochemical performances as anode for Li‐ion batteries were characterized by X‐Ray Diffraction (XRD), Raman, X‐ray photoelectron spectrometer (XPS), Scanning Electron Microscope (SEM), and other means. It is found that coating process does not affect the phase structure but influences the morphology, specific area, and electrochemical performances. HC/P series have abundant pores with diameter of 2 to 5 nm and small‐size particles; thus, they have much more lithium storage position or charge/discharge capacity than pristine hard carbon (HC). Besides, Cyclic Voltammetry (CV) curves of HC/P‐2 proved that the irreversible side reactions of Li + with surface functional groups were reduced, which can explain the advancement of initial coulomb efficiency. Among three HC/P samples, HC/P‐2 owns the best electrochemical performances. It delivered 520 mAh/g under current density of 20 mA/g and kept 95.9% retention rates of capacity after 100 cycles under 200 mA/g of current density. Abstract : From the HRTEM and SAED results of HC/P‐2, the carbon layer of pyrolytic PVDF is apparent, with thickness about 4 to 5 nm. Moreover, the HC/P series, which are coated by different amount of pyrolytic PVDF, has higher charge/discharge capacity, better initial coulomb efficiency, and smaller hysteresis voltage than pristine hard carbon. It was proved that pyrolytic carbon of PVDF improves surface condition of pristine hard carbon and enhances the electronic conductivity. It is an efficient method to advance electrochemical performances of hard carbon and propel its practical application.